A critical analysis of section 6(4) of the Employment Equity ACT: is it likely to achieve its stated objectives? - Maharaj, Pranisha (Department of Commercial Law, 2020)
This dissertation presents a critical analysis of section 6(4) of the Employment Equity Act 55 of 1998 (“EEA”) and seeks to address the question of whether it is likely to achieve its stated objective of giving effect to the constitutional right to equality. In conducting my analysis, I consider the concept of managerial prerogative and discuss what underlies the drive for substantive equality in order to determine why the issue of protection from discriminatory income disparities has been removed from the realm of an employer’s traditional prerogative. Next, I highlight the requirements for establishing a claim of discrimination in terms section 6(4) and the remedies available to a successful complainant. I then turn to highlight the limitations introduced by the statutorily prescribed comparator in section 6(4) before demonstrating that the regulated methodology for assessing the value of work and the factors for justifying a differentiation in terms and conditions of employment give significant deference to employer prerogative. My analysis proceeds to consider whether, following the introduction of section 6(4), an administrative body whose primary function is the conduct of formal investigation into discriminatory pay practices and the resolution of equal pay disputes ought to have been created. I ultimately conclude that section 6(4) of the EEA provides only a partial solution to the issue of discriminatory pay disparities in South Africa and is likely to have a limited effect in contributing to the achievement of the State’s objective of achieving substantive equality. In analysing section 6(4), I draw on the experience of the United Kingdom, the United States of America and Canada. While the socio-economic and political landscapes of these jurisdictions may not be apposite to the South African experience, these jurisdictions have a long legislative history in pay equality issues which assist in establishing a benchmark for South Africa.